Self-Presentation and Its Relationship to Personal Competence among University Students - Yaser Maktoof, Sabeeha (Journal of College of Education, 2021)
The aim of the research is to identify both the self-presentation and the personal competence of university students, test the relationship between them and to reveal the differences in self-presentation according to the variable (gender - specialization) as well as the differences in personal competence according to the variable (gender - specialization). The basic research sample is (300) male and female students: (150) males and (150) females. A self-presentation scale which was used by (Yarzer and Haitham) has been adopted in this research. While the researcher prepared a measure of personal competence. The data were processed using the statistical means (SPSS). The researcher finds that: The level of self-presentation among university students is within the average level, as well as the personal competence of university students. There is a statistically significant relationship between self-presentation and personal competence among university students. There is a statistically significant difference in self-presentation according to the gender variable and in favor of males, as well as there is no statistically significant difference according to specialization. There is no statistically significant difference in personal competence according to the gender variable, as well as the specialization of university students. The researcher put forward a number of recommendations, including the need for the Ministry of Higher Education to pay attention to the establishment of courses that contribute to raising the level of self-presentation of students. The researcher also set a number of suggestions, including conducting a study on self-presentation and its relationship to academic achievement among university students.